The Role of Counseling Services in Improving Athlete Achievement - Rika Sepriani; Neviyarni S; Mudjiran -; Herman Nirwana (Universitas Negeri Padang, 2021)
Athletes are people who participated in sports activities that were planned, measured, and recorded in order to achieve success. A goal achieved to the best of one's ability is referred to as achievement. To achieve high levels of athletic achievement, all aspects of physical, technical, tactical, and mental conditioning must be trained and programmed in a systematic and planned manner. Unfortunately, athletes' mental development is frequently neglected and underutilized compared to other aspects, resulting in athletes who are less able to manage problems that may interfere with their success. Counseling can assist athletes in managing their problems correctly and achieving peak performance. The focus of sports counseling services includes athlete mental readiness, motivation, and peak performance. Counseling will be provided following the principles of confidentiality, volunteerism and openness, independence, modernity, and normativeness. The uniqueness, potential, and problems that impede the development of an athlete's achievement can be minimized with counseling services, allowing athletes to perform optimally.